Epidemiological profile of animal bite patients attending emergency department at a tertiary care health facility in a northern hilly Indian city - Kumar, Sanjay; Gupta, Anmol; Sachdeva, Amit; Chaudhary, Ankit; Chamotra, Shaina (International Journal Of Community Medicine And Public Health, 2019)
Background: Rabies is a highly infectious zoonotic disease with a high case fatality rate. In India, approximately 20,000 deaths among 17.4 million exposed people occur every year. The data on animal bites is scarce and unreliable due to poor surveillance and hence, the projected figures are far less from the actual numbers. The present study was conducted to describe epidemiological characteristics of animal bite patients attending casualty department at a tertiary care Government health facility in Shimla, Himachal Pradesh. Methods: It was a retrospective study based on secondary data received from animal bite register for year 2017 at casualty department of the Indira Gandhi Medical College and Hospital, Shimla, Data of 1512 patients attending the casualty department with history of animal bite was included for the study purpose. Results: About 58% of victims were males and the maximum (22.6%) animal bites were seen in 21-30 years age group. Majority (51.6%) of patients were exposed to dog bites, followed by monkey bites (42.85%) and cat bite 49 (3.2%). About 69.9% of animal bites were in the lower limbs, followed by upper limbs (22.1%), abdomen (4.4%) and head and neck region (3.6%). Maximum bites were category III bites (74.6%) followed by of category II bites (12.9%). Conclusions: Study highlights the neglected but significant picture of animal bite in the Shimla city. Timely and correct post exposure prophylaxis for the animal bite victims is necessary to prevent rabies. This should be supplemented with a robust surveillance and reporting system. With the global aim of zero rabies deaths by 2030; it is time to strengthen the anti-rabies activities at every level.